Photodynamic Therapy in the Extracellular Matrix of Mouse Lungs: Preliminary Results of an Alternative Tissue Sterilization Process - Luis Vicente Franco Oliveira; Nadua Apostólico; Juan José Uriarte; Renata Kelly da Palma; Renato A. Prates; Alessandro Melo Deana; Luis Rodolfo Ferreira; João Pedro Ribeiro Afonso; Rodolfo de Paula Vieira; Manoel Carneiro de Oliveira Júnior; Daniel Navajas; Ramon Farré; et al. (International Journal of Photoenergy)
Lung transplantation is one of the most difficult and delicate procedures among organ transplants. For the success of the procedure and survival of the new organ, the sterilization step for acellular lungs prior to recellularization is important to ensure that they are free of any risk of transmitting infections from the donor to the recipient subject. However, there are no available information concerning the lung mechanical parameters after sterilizing photodynamic therapy. The aim of this study was to evaluate the extracellular matrix (ECM) and lung mechanical parameters of decellularized lungs undergoing sterilizing photodynamic therapy (PDT). Besides, we also analyzed the lung after controlled infection with C. albicans in order to evaluate the effectiveness of PDT. The lung mechanical evaluation parameters, resistance (RL) and elastance (EL), exhibited no significant differences between groups. In addition, there were no PDT-induced changes in lung properties, with maintenance of the viscoelastic behavior of the lung scaffold after 1 h exposure to PDT. The ECM components remained virtually unchanged in the acellular lungs of both groups. We also showed that there was a reduction in fungal infection population after 45 minutes of PDT. However, more studies should be performed to establish and verify the effectiveness of PDT as a possible means for sterilizing lung scaffolds. This manuscript was presented as a master thesis of Nadua Apostólico at the postgraduate program in rehabilitation sciences, University Nove de Julho—UNINOVE.